Social and spatial impacts of changing urban form in Ayazaga, Turkey - Kirtas, Emine Ecem; Tomruk, Banu (INT SEMINAR URBAN FORM, 2023)
The politics of spatial reproduction have been at the heart of Turkey's economic growth over the past two decades, accelerating rapid urban change in istanbul. In addition to the transformation of the existing building stock in the city, natural spaces are also being developed through the partial revision of master plans and reproduced through large- scale new investments. This study examines the spatial changes in the Ayazaga Neighbourhood on the northern periphery of istanbul. The region has become one of the areas where large capital owners have invested extensively in the last decade. Most of the new spatial interventions are large- scale mixed- use buildings. Based on morphological analysis and in- depth interviews with residents, the study investigates the existing urban fabric and the new interventions through four specific cases. The reproduction of urban space in the case study areas is discussed in terms of spatial characteristics and social aspects. As a result, the lack of public open spaces, massive new buildings with privately owned public spaces, and the social and spatial segregation between the residents of the informal settlements and the new upper- class housing are addressed as problem areas.
Keywords: piecemeal urbanism; top-down interventions; urban form transformation; spatial segregation; istanbul; MORPHOLOGY; Architecture